2022
DOI: 10.5194/bg-2022-45
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First phytoplankton community assessment of the Kong Håkon VII Hav, Southern Ocean during austral autumn

Abstract: Abstract. We studied phyto- and protozooplankton community composition based on light microscopy, flow cytometry and photosynthetic pigment data in the Atlantic sector of the Southern Ocean during March 2019 (early austral autumn). Sampling was focused on the area east of the prime meridian in the Kong Håkon VII Hav, including Astrid Ridge, Maud Rise and a south-north transect at 6° E. Phytoplankton community composition throughout the studied area was characterized by oceanic diatoms typical of the iron-deple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The sea-ice retreat at the SIZ-PAZ boundaries triggers ice edge blooms (Lancelot et al, 1993;Smith & Nelson, 1985). Ship-based studies have reported enhanced levels of chl-a just north of the ice edge in early December, where large diatoms are abundant in the southern PAZ, while small pennate diatoms and Phaeocystis dominate in the SIZ (Kauko et al, 2022;Landry et al, 2002). Although the SIZ shows higher values of POC (Fig.…”
Section: Contrast In Biological Seasonality Between Zonesmentioning
confidence: 95%
“…The sea-ice retreat at the SIZ-PAZ boundaries triggers ice edge blooms (Lancelot et al, 1993;Smith & Nelson, 1985). Ship-based studies have reported enhanced levels of chl-a just north of the ice edge in early December, where large diatoms are abundant in the southern PAZ, while small pennate diatoms and Phaeocystis dominate in the SIZ (Kauko et al, 2022;Landry et al, 2002). Although the SIZ shows higher values of POC (Fig.…”
Section: Contrast In Biological Seasonality Between Zonesmentioning
confidence: 95%